Deception and Manipulation: The Arms of Leishmania, a Successful Parasite - Cecílio, Pedro; Pérez-Cabezas, Begoña; Santarém, Nuno; Maciel, Joana; Rodrigues, Vasco; Cordeiro da Silva, Anabela (Frontiers in Immunology, 2014)
Leishmania spp. are intracellular parasitic protozoa responsible for a group of neglected tropical diseases, endemic in 98 countries around the world, called leishmaniasis. These parasites have a complex digenetic life cycle requiring a susceptible vertebrate host and a permissive insect vector, which allow their transmission. The clinical manifestations associated with leishmaniasis depend on complex interactions between the parasite and the host immune system. Consequently, leishmaniasis can be manifested as a self-healing cutaneous affliction or a visceral pathology, being the last one fatal in 85-90% of untreated cases. As a result of a long host-parasite co-evolutionary process, Leishmania spp. developed different immunomodulatory strategies that are essential for the establishment of infection. Only through deception and manipulation of the immune system, Leishmania spp. can complete its life cycle and survive. The understanding of the mechanisms associated with immune evasion and disease progression is essential for the development of novel therapies and vaccine approaches. Here, we revise how the parasite manipulates cell death and immune responses to survive and thrive in the shadow of the immune system.